Where Nation-States Come From : Institutional Change in the Age of Nationalism - Roeder, Philip G. (Book collections on Project MUSE., 2007)
Almost all successful nation-state projects have been associated with a particular political institution prior to independence - the segment-state. This text clarifies this link through narrative evidence from Central Eurasia, a rigorous theory, and extensive statistical tests.